THE INFLUENCE OF WORK DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN BRANCH OF SIMPANG RAYA RESTAURANT IN SERANG CITY - Ami Sundari (Amal Insani Foundation, 2020)
This study aims to determine: (1) the effect of work discipline on employee performance at Simpang Raya Restaurant in Serang City, (2) the effect of work motivation on employee performance at Simpang Raya Restaurant in Serang City, and (3) the effect of work discipline and work motivation on performance. employees of the Simpang Raya Restaurant in Serang City. This research is a causal associative research using a quantitative approach. Sampling using saturated sampling, meaning that the entire population is used as a sample. The data collection technique used is a questionnaire whose measurement uses a Likert scale and is statistically processed using multiple regression analysis methods with equations through the IBM SPSS Statistics 23.0 program. The results showed that: (1) partially Work Discipline has a positive and significant effect on the employee performance of Simpang Raya Restaurant in Serang City. This is evidenced by the results with t count 2.087> t table 1.695 and significant 0.045 <0.05. (2) partially work motivation has a positive and significant effect on employee performance of Simpang Raya Restaurant in Serang City. This is evidenced by the results with t count 2.728> t table 1.695 and significant 0.010 <0.05. (3) Discipline and motivation simultaneously have a positive and significant effect on employee performance. This can be seen from F count> F table, namely F count 8,092> 3.30, so F count> F table significant 0.001. The influence of discipline and work motivation variables on employee performance is 34.3%, indicated by the R2 value of 0.343